2015
DOI: 10.1038/ncomms7443
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling spatial and temporal soil moisture effects on afternoon rainfall

Abstract: Soil moisture impacts on precipitation have been strongly debated. Recent observational evidence of afternoon rain falling preferentially over land parcels that are drier than the surrounding areas (negative spatial effect), contrasts with previous reports of a predominant positive temporal effect. However, whether spatial effects relating to soil moisture heterogeneity translate into similar temporal effects remains unknown. Here we show that afternoon precipitation events tend to occur during wet and heterog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
362
3
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 311 publications
(384 citation statements)
references
References 44 publications
(91 reference statements)
18
362
3
1
Order By: Relevance
“…This resolution has been shown to be sufficient to resolve deep convection (no convective parameterization is used) and to correctly represent the sign and magnitude of the land−atmosphere interaction feedback (18), contrary to GCMs, which tend to exhibit soil moisture−precipitation feedbacks of opposite sign to that observed (19). We parameterize the time-dependent large-scale vertical motion as a function of internally resolved convection using the weak temperature gradient (WTG) approximation (Methods).…”
Section: Resultsmentioning
confidence: 99%
“…This resolution has been shown to be sufficient to resolve deep convection (no convective parameterization is used) and to correctly represent the sign and magnitude of the land−atmosphere interaction feedback (18), contrary to GCMs, which tend to exhibit soil moisture−precipitation feedbacks of opposite sign to that observed (19). We parameterize the time-dependent large-scale vertical motion as a function of internally resolved convection using the weak temperature gradient (WTG) approximation (Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Counterintuitive effects of explicit entrainment can also introduce exotic behaviors [Hohenegger et al, 2009]. Thus, both positive and negative soil moisture feedback on precipitation can occur as shown in many studies [Hohenegger et al, 2009;Findell et al, 2011;Taylor et al, 2011Taylor et al, , 2012Gentine et al, 2013c;Guillod et al, 2015].…”
Section: Introductionmentioning
confidence: 98%
“…These studies range in spatial and temporal scales and use a combination of models, reanalysis or satellite products [e.g., Dirmeyer, 2006Dirmeyer, , 2011Dirmeyer et al 2012;Findell et al, 2011;Taylor et al, 2012], with associated trade-offs. For instance, observational-based analyses are limited by an inability to explore the relationship of causality and short temporal and sparse spatial coverage, while reanalysis and models are impaired by their PBL and cloud parameterization schemes [Seneviratne et al, 2010;Ferguson et al, 2012;Guillod et al, 2015], though this can be mitigated to some degree by assimilating rainfall data [Findell et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other areas of the world the synoptic forcing is usually so strong that a robust relationship of causality between soil moisture and precipitation cannot be found (Tuttle and Salvucci, 2017). Instead of speaking of heterogeneous or homogeneous conditions, Guillod et al (2015) have indicated that over most areas of the world, except the Sahel, a negative spatial coupling coexists together with a positive temporal coupling. That is, areas drier than their surroundings (spatial component) but wetter than the climatological value (temporal component) may receive more precipitation than other areas.…”
Section: Introductionmentioning
confidence: 99%